2020
DOI: 10.2147/ijwh.s278508
|View full text |Cite
|
Sign up to set email alerts
|

<p>Magnitude and Associated Factors of Institutional Delivery Among Reproductive Age Women in Southwest Ethiopia</p>

Abstract: Background: Despite the global maternal mortality ratio (MMR) fallen by nearly 44% from 1990 to 2015, however, maternal mortality remains a global problem. Reducing maternal morbidity and mortality is a global priority, which is particularly relevant for developing countries like Ethiopia. A good strategy for reducing maternal morbidity and mortality is increasing institutional delivery service utilization. This study aimed to assess the magnitude and associated factors of institutional delivery among reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 21 publications
7
11
0
Order By: Relevance
“…Mothers who received antenatal care had 73% higher odds of institutional delivery, compared to those who did not receive antenatal care. This finding is aligned with the studies from Ethiopia ( 36 , 58 60 ), Pradesh, India ( 61 ), Tanzania ( 62 ), and Bangladesh ( 63 ). One of the services given by ANC includes counseling for the place of delivery preparation ( 64 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mothers who received antenatal care had 73% higher odds of institutional delivery, compared to those who did not receive antenatal care. This finding is aligned with the studies from Ethiopia ( 36 , 58 60 ), Pradesh, India ( 61 ), Tanzania ( 62 ), and Bangladesh ( 63 ). One of the services given by ANC includes counseling for the place of delivery preparation ( 64 ).…”
Section: Discussionsupporting
confidence: 89%
“…The study found the overall magnitude of institutional delivery 45.03% with 95% CI (44.33-45.72). This finding was higher than studies conducted in Afar, Ethiopia (35%) (12), in the Gurage zone, Ethiopia (31%) (35), and lower than studies done in Southwest Ethiopia (76%) (36), and South Ethiopia (74%) (10). Studies revealed that socio-demographic factors such as residence area, nearness of health facility, and maternal education can affect the level of maternal health care utilization, particularly institutional deliveries (37,38).…”
Section: Discussionmentioning
confidence: 72%
“…There was high variation throughout different administrative levels in the country. For instance, institutional delivery was 72% in Bule Hora in Oromiya [ 18 ]; 89.1% in Damot district in SNNP [ 19 ]; 61.5% in North-Western part of the country [ 20 ]; 76% in Southwest Ethiopia [ 21 ]; 71.7% in Dejen Woreda; 78.8% in Bahir Dar [ 22 ]; 18.3% in Dangila woreda; 47% in semi-urban parts of the country [ 23 ]; 38% in Mandura district [ 24 ]; 53% in Hossana town [ 25 ]; 74% in Dallocha town [ 26 ] and 49% in Hetosa district [ 27 ]. The rate of increase was 5.4% in 2000 and 11.8%,2011 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Younger mothers are more likely to be prepared/educated and have better access to knowledge than older mothers, which may be the cause. A study conducted among Arsi, 12 Southwest Ethiopia, 33 Bahir-Dar, 13 Tigray, 14 Northwest Ethiopia, 15 Sekela District 16 and Holeta Town 17 supports this finding. Besides, institution delivery service use was significantly linked to the mother's education level and husbands' education level.…”
Section: Discussionmentioning
confidence: 84%